Aplikasi Mobile Deteksi Gangguan Mental dengan Integrasi Metode Forward Chaining dan Certainty Factor Menggunakan Rapid Application Development RAD - Fergina, Anggun; Pebrian, Riko; Adela, Dhea (LPPM STIKOM Tunas Bangsa, 2024)
Mental disorders represent a serious public health challenge, requiring effective approaches to prevention and early recognition. Limitations in access to mental health services, such as distance, cost, and social stigma, prevent individuals from getting professional help. The system developed in this research provides an early detection solution through collecting data from questionnaires and other health information. Implementation of the Certainty Factor method measures the level of belief in symptoms of mental disorders, while Forward Chaining produces diagnoses and recommendations for action. The system integrates data from various sources, including user activity on digital platforms, making a significant contribution to technology supporting the management of mental disorders. This research is supported by literature studies and uses Unified Modeling Language (UML) for software design, strengthening the theoretical foundation in overcoming mental disorders..